Assessment on functionality and viability of β cells following repetitive dosage administration of ethanolic extracts of andrographis paniculata on streptozotocin-induced diabetic rats. - Kasmuri, Abdul Razak; Ahmad, Mariam; Sadikun, Amirin; Asmawi, Mohd Zaini (Faculty of Medicine, International Islamic University Malaysia, 2010)
Introduction: The study was done at the aim to assess the functionality and viability of the β cells of the streptozotocin-induced diabetic rats model following repetitive dosage of administration of ethanolic extracts of Andrographis paniculata. Materials and Methods: The diabetic rats were treated with the extracts for fourteen days and at the dose given was 500 mg/kg twice daily. The assessments were made on fasting blood glucose, insulin, and immunohistochemical aspect of β cells before and after treatment. Results: The results showed that there was a signifi cant reduction on fasting blood glucose levels in metformin, 95% and 50% ethanolic plant extracts-treated groups but on insulin level only 95% and 50% ethanolic extracts-treated groups gave a signifi cant reduction (p<0.05). Immunohistochemical assessments revealed that all extract groups and metformin-treated were signifi cantly increased in the population of β cells (p<0.01). Conclusion: This study revealed that the plant extracts showed an ability to promote the growth or rejuvenate the STZdestructed β cells and in turn lower the blood glucose level.